Relationship Knowledge and Attitude of Mom and Family Support in Doing Baby Massage Independently in Puskesmas District Onowaembo Help Gunungsitoli In 2021 - magdalena Barus; Mediana Sembiring (Science Midwifery, 2022)
Baby massage is a touch therapy in direct contact with the body that can provide a sense of security and comfort for babies. Mother's broad knowledge will also affect the mother's desire to do baby massage, besides that there are also work factors, attitudes and perceptions that can influence in doing baby massage. This type of research uses an analytical research design with a cross-sectional approach, which is a type of research with cause or risk and effect variables or cases that occur when the research object is measured or collected simultaneously (at the same time). which can be obtained from this research, namely, Based on the results of research that has been carried out on the Relationship of Mother's Knowledge with Mother's Independence to Doing Baby Massage independently, the results of the Chi-Square test, the significant value of the relationship between mother's knowledge and mother's independence is 0.000, which means p-value < 0.05. So, it can be concluded that there is a significant relationship between mother's knowledge and mother's independence. Based on the results of research that has been carried out on the relationship between mother's attitude and mother's independence towards doing baby massage independently, the result of the Chi-square test is that the significant value of the relationship between mother's attitude and mother's independence is 0.000 , which means p-value <0.05. So, it can be concluded that there is a significant relationship between mother's attitude and mother's independence. Based on the results of research that has been carried out on the relationship between family support and mother independence on doing baby massage independently, the Chi-square test result shows that the significant value of the relationship between family support and mother's independence is 0.000, which means p-value <0.05. So, it can be concluded that there is a significant relationship between family support and maternal independence. This is in line with Malikhotul's research (2012) on "The relationship between mother's level of knowledge about infant massage and infant massage behavior at the Posyandu, Gunungsari Village, Beji District, Pasuruan Regency. This study shows that mother's knowledge about infant massage is related to infant massage behavior. It is hoped that health workers, especially midwives.